COOKING SUPPORT SYSTEM, COOKING SUPPORT METHOD, INFORMATION TERMINAL, AND PROGRAM - MUTA MIKIHIKO; KAMIYA MIYUKI; AKIOKA NAOKATSU; OKAMOTO HIDEKI; TOYODA KAZUKI; FUJII GEN (2023)
To provide a cooking support system for more accurately determining suitability in each cooking process when a cook performs cooking.SOLUTION: A cooking support system 1 includes a progress status acquisition unit 11, a mental state estimation unit 12, and a determination unit 13. The progress status acquisition unit 11 acquires progress of cooking including a plurality of cooking processes. The mental state estimation unit 12 estimates a mental state of a cook in each of a plurality of cooking processes based on physiological information of the cook who performs cooking. The determination unit 13 determines suitability of the cook in each of the plurality of cooking processes based on the mental state.SELECTED DRAWING: Figure 1 【課題】調理人が調理を行う際の各調理工程において、適性度をより正確に判定する調理支援システムを提供する。【解決手段】調理支援システム１は、進捗状況取得部１１と、心理状態推定部１２と、判定部１３と、を備える。進捗状況取得部１１は、複数の調理工程を含む調理の進捗を取得する。心理状態推定部１２は、調理を行う調理人の生理情報に基づき、複数の調理工程の各々における調理人の心理状態を推定する。判定部１３は、心理状態に基づいて、複数の調理工程の各々における調理人の適性度を判定する。【選択図】図１